2006
DOI: 10.1021/jf053169a
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Absorption and Urinary Excretion of trans-Cinnamic and p-Coumaric Acids in Rats

Abstract: trans-Cinnamic acid (CIN) and p-coumaric acid (COU) are ingested by humans in their diet. While the metabolism and health benefits of CIN have been widely documented, little is known about its absorption sites, and there have been few studies dedicated to COU. The gastrointestinal sac technique demonstrated that CIN and COU are absorbed by all digestive organs in rats and partially transported via MCT-mediated carrier. Absorption was lowest in the stomach. Regardless of the organs that were studied, CIN was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 34 publications
(52 reference statements)
3
37
0
Order By: Relevance
“…In sacrificed rats, CIN was rapidly absorbed by the digestive tract and, as previously reported (19), the gastrointestinal sac technique shows that all the digestive organs absorb CIN. It is known that CIN is partially transported across either the various digestive organs (19) or Caco-2 cell monolayers (25) by a carrier-mediated transport process. The present study demonstrates a faster and more extensive absorption of CIN in sacrificed rats than that found in gastrointestinal sacs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In sacrificed rats, CIN was rapidly absorbed by the digestive tract and, as previously reported (19), the gastrointestinal sac technique shows that all the digestive organs absorb CIN. It is known that CIN is partially transported across either the various digestive organs (19) or Caco-2 cell monolayers (25) by a carrier-mediated transport process. The present study demonstrates a faster and more extensive absorption of CIN in sacrificed rats than that found in gastrointestinal sacs.…”
Section: Discussionsupporting
confidence: 75%
“…5). It is known that COU is absorbed according to passive and active transport across either Caco-2 cell monolayers (25,26) or the intestinal digestive epithelium of rats (19,27). The CA4H activity observed ex vivo was some seven times higher than that detected in sacrificed rats.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…PA, FA and CA quickly disappeared from the jejunum, and to a lesser extent from the ileum, when they were perfused in an isolated rat intestine model (Spencer et al 1999). Another in vitro study using gastrointestinal sac techniques showed that PA can be absorbed in all sections of the gastrointestinal tract, with the highest absorption rate in the jejunum (Garrait et al 2006). The type of HC is another factor to determine their absorption rate (Table 1).…”
Section: Uptake and Absorptionmentioning
confidence: 99%
“…During its metabolism, HC may undergo a number of enzymatic reactions including dehydroxylation, demethylation, dehydrogenation, hydrogenation, O-methylation, sulphation, glucuronization, GSH conjugation, and/or glycination (Table 2; Scheline 1968; Scheline and Midtvedt 1970;Gumbinger et al 1993;Spencer et al 1999;Chesson et al 1999;Gonthier et al 2003Gonthier et al , 2006Olthof et al 2001Olthof et al , 2003dos Santos et al 2005;Zhao et al 2003a, b;Manach et al 2004;Poquet et al 2008b;Garrait et al 2006;Lafay et al 2006a, b;Zhao and Moghadasian 2008).…”
Section: Metabolismmentioning
confidence: 99%